2019
DOI: 10.3390/molecules24101972
|View full text |Cite
|
Sign up to set email alerts
|

The Mutation of Conservative Asp268 Residue in the Peptidoglycan-Associated Domain of the OmpA Protein Affects Multiple Acinetobacter baumannii Virulence Characteristics

Abstract: Acinetobacter baumannii is a nosocomial human pathogen of increasing concern due to its multidrug resistance profile. The outer membrane protein A (OmpA) is an abundant bacterial cell surface component involved in A. baumannii pathogenesis. It has been shown that the C-terminal domain of OmpA is located in the periplasm and non-covalently associates with the peptidoglycan layer via two conserved amino acids, thereby anchoring OmpA to the cell wall. Here, we investigated the role of one of the respective residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…We found the ompA knockout associated with a significant decrease in pellicle formation in ATCC 17978 but not in 29D2. For A. baumannii and a number of other pathogens, OmpA has been identified as a virulence factor [97][98][99]. In our study, the knockout of ompA in both tested strains significantly decreased the mutant's ability to kill G. mellonella.…”
Section: Outer Membrane Proteinsmentioning
confidence: 49%
“…We found the ompA knockout associated with a significant decrease in pellicle formation in ATCC 17978 but not in 29D2. For A. baumannii and a number of other pathogens, OmpA has been identified as a virulence factor [97][98][99]. In our study, the knockout of ompA in both tested strains significantly decreased the mutant's ability to kill G. mellonella.…”
Section: Outer Membrane Proteinsmentioning
confidence: 49%
“…In contrast to biofilm formation and adhesive properties, our study showed the importance of both blp1 variants for the host colonization of respective strains and, in addition, the requirement of the cognate allele for the manifestation of this phenotype in IC I strain. Several studies have demonstrated the allele-dependent variations in virulent properties of bacterial pathogens [19, 28, 29]. Therefore, the Blp1 may possess yet unknown function required for host colonization, different from that mediating the adhesive properties, which appear to be redundant in IC II strain.…”
Section: Discussionmentioning
confidence: 99%
“…A. baumannii strain Ab 169 and its ompA deletion mutant were described in a previous study [ 17 ]. OMVs were isolated as described by [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…A. baumannii strain Ab 169 and its ompA deletion mutant were described in a previous study [ 17 ]. OMVs were isolated as described by [ 17 ]. Briefly, 130 mL of bacterial culture in LB medium grown for 20 h at 37 °C was centrifuged for 15 min at 10,000× g at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation